Different social influences and desistance from crime - Abeling-Judge, David (Criminal justice and behavior, 2016)
Desistance from crime has been associated with numerous social influences. Although researchers have explored different theoretical rationales and underlying mechanisms between external social developments and individual changes in behavior, little focus has been given to the individual versus cumulative influences, and social complexities, of different informal controls influencing reduction in criminal behavior. The current study explores the individual and combined impact of marriage and employment on arrest using 17 years of monthly level data from the National Longitudinal Survey of Youth (1997). The results address isolated and cumulative influences of each social control on arrest and provide insight into the relevance of acknowledging the complexities of social events developing over time.